2008
DOI: 10.1007/s10585-008-9141-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sentinel lymphadenectomy on survival in a murine model of melanoma

Abstract: Lymphatic mapping and sentinel lymph node biopsy-also termed sentinel lymphadenectomy (SL)-has become a standard of care for patients with primary invasive cutaneous melanoma. This technique has been shown to provide accurate information about the disease status of the regional lymph node basins at risk for metastasis, provide prognostic information, and provide durable regional lymph node control. The potential survival benefit afforded to patients undergoing SL is controversial. Central to this controversy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…Much discussion has focused on the origins of metastases in melanoma. Studies have shown that in animal models of melanoma, pulmonary metastases occur even in the absence of lymph node metastases, underscoring a potential difference between hematogenous and lymphatic routes of tumor cell dissemination (22). In support of this, recent studies have shown that even though younger patients develop more sentinel lymph node metastases than older patients, outcome is poorer for older patients, due to increased visceral metastases (23).…”
Section: Discussionmentioning
confidence: 99%
“…Much discussion has focused on the origins of metastases in melanoma. Studies have shown that in animal models of melanoma, pulmonary metastases occur even in the absence of lymph node metastases, underscoring a potential difference between hematogenous and lymphatic routes of tumor cell dissemination (22). In support of this, recent studies have shown that even though younger patients develop more sentinel lymph node metastases than older patients, outcome is poorer for older patients, due to increased visceral metastases (23).…”
Section: Discussionmentioning
confidence: 99%
“…Third, recent clinical trials showed significant benefit for patients with small melanoma tumors who underwent lymphadenectomy immediately, thus disputing the previous conclusion [114]. Fourth, experimental assessment of this question in a melanoma model also showed significant survival benefit of sentinel lymphadenectomy for mice bearing small tumors [115]. The same study also found that cells from primary tumors and sLN have equal metastatic potential to colonize distant organs [115], thus arguing against the hypothesis that nodal metastatic cells are biologically restricted to their first destination site.…”
Section: Clinical Evidence For Association Of Lymphangiogenesis Anmentioning
confidence: 99%
“…Fourth, experimental assessment of this question in a melanoma model also showed significant survival benefit of sentinel lymphadenectomy for mice bearing small tumors [115]. The same study also found that cells from primary tumors and sLN have equal metastatic potential to colonize distant organs [115], thus arguing against the hypothesis that nodal metastatic cells are biologically restricted to their first destination site. Lastly, much of the recent information on tumor lymphatic biology directly contradicts the opinion that metastatic cells in the lymph nodes “venture no farther” [116].…”
Section: Clinical Evidence For Association Of Lymphangiogenesis Anmentioning
confidence: 99%
“…A murine model of sentinel lymph node metastasis on the basis of injection of human melanoma cells into the preauricular area of athymic nude mice was created as described previously [14]. The present study was performed under protocols approved by the Animal Care and Use Committee of the College of Medicine of Yonsei University.…”
Section: Human Melanoma Xenograft Modelmentioning
confidence: 99%